2020
DOI: 10.3389/fonc.2020.01503
|View full text |Cite
|
Sign up to set email alerts
|

A New Prognostic Index Combines the Metabolic Response and RECIST 1.1 to Evaluate the Therapeutic Response in Patients With Non-Small Cell Lung Cancer

Abstract: Aim: Response Evaluation Criteria in Solid Tumors (RECIST) is occasionally insufficient for evaluation. We proposed a new prognostic index (NPI) that combines the standardized uptake value (SUV), metabolic tumor volume (MTV), and RECIST. Methods: In total, 116 patients with lung cancer who underwent consecutive positron emission tomography-computed tomography prior to and after the initial treatment were included. We formulated the NPI by estimating the hazard ratios of overall survival for MTV, SUV max , and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 32 publications
(39 reference statements)
0
1
0
Order By: Relevance
“…At present, Response Evaluation Criteria in Solid Tumours (RECIST) is the gold standard for evaluating the efficacy of therapeutic interventions for lung cancer, with changes in tumour volume after treatment assessed by computed tomography (CT) or other radiographic methods to determine the curative effect. However, in contrast to cytotoxic chemotherapy, the mechanisms of action of targeted therapy and immunotherapy do not involve killing tumour cells directly, so the changes in tumour volume associated with these therapies usually occur later than the changes in functional indicators (4,5). It has been reported that the histopathological response of 41-45% of patients may be inconsistent with the results of CT evaluation (6).…”
Section: Introductionmentioning
confidence: 99%
“…At present, Response Evaluation Criteria in Solid Tumours (RECIST) is the gold standard for evaluating the efficacy of therapeutic interventions for lung cancer, with changes in tumour volume after treatment assessed by computed tomography (CT) or other radiographic methods to determine the curative effect. However, in contrast to cytotoxic chemotherapy, the mechanisms of action of targeted therapy and immunotherapy do not involve killing tumour cells directly, so the changes in tumour volume associated with these therapies usually occur later than the changes in functional indicators (4,5). It has been reported that the histopathological response of 41-45% of patients may be inconsistent with the results of CT evaluation (6).…”
Section: Introductionmentioning
confidence: 99%